2022
DOI: 10.1097/md.0000000000029881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of idiopathic erythrocytosis on the left ventricular diastolic functions and the spectrum of genetic mutations: A case control study

Abstract: Background: We have aimed at exposing left ventricular diastolic functions and the presence of known genetic mutations for familial erythrocytosis, in patients who exhibit idiopathic erythrocytosis. Methods: Sixty-four patients with idiopathic erythrocytosis (mean age, 46.4 ± 2.7 years) and 30 age-matched healthy subjects were prospectively evaluated. The regions of interest of the erythropoietin receptor, hemoglobin beta-globin, von Hippel-Lindau, hypoxia-inducible fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…71,74 A cohort of patients with IE were found to have reduced left ventricular function when compared with controls. 78 A population-based study with 20-year follow-up showed haemoglobin in the highest quartile to be an independent risk factor for cardiovascular-related (HR 2.08) and overall mortality (HR 1.48) when adjusted for age, sex, lifestyle and metabolic factors. 77 The nature of the relationship between haemoglobin/ haematocrit levels and these comorbidities is unclear.…”
Section: W H At L E Ssons Ca N Be L E a R N E D From Th E Associ Atio...mentioning
confidence: 99%
See 1 more Smart Citation
“…71,74 A cohort of patients with IE were found to have reduced left ventricular function when compared with controls. 78 A population-based study with 20-year follow-up showed haemoglobin in the highest quartile to be an independent risk factor for cardiovascular-related (HR 2.08) and overall mortality (HR 1.48) when adjusted for age, sex, lifestyle and metabolic factors. 77 The nature of the relationship between haemoglobin/ haematocrit levels and these comorbidities is unclear.…”
Section: W H At L E Ssons Ca N Be L E a R N E D From Th E Associ Atio...mentioning
confidence: 99%
“…Haemoglobin has also been associated with increased serum uric acid levels 71,74 . A cohort of patients with IE were found to have reduced left ventricular function when compared with controls 78 . A population‐based study with 20‐year follow‐up showed haemoglobin in the highest quartile to be an independent risk factor for cardiovascular‐related (HR 2.08) and overall mortality (HR 1.48) when adjusted for age, sex, lifestyle and metabolic factors 77 …”
Section: What Lessons Can Be Learned From the Association Of Elevated...mentioning
confidence: 99%